1994
DOI: 10.2486/indhealth.32.57
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Indices of Visual Fatigue due to VDT Operation: Pupillary Reflexes and Accommodative Responses.

Abstract: In spite of the clarification of some significant physiological factors of visual fatigue caused by VDT work, pupillary reflexes have not been studied as to how they are affected after prolonged visual work. This study examined visual function changes objectively in terms of pupillary reflexes and lens accommodative responses after a 4-hr VDT operation task. The relationship between the two functions was also examined.Two measurements in this paper revealed the physiological function changes due to VDT operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 6 publications
6
39
1
1
Order By: Relevance
“…This result was in accordance with our previous report 5 on 2DD. A similar result has been reported from another laboratory, 10 where a systematic prolongation of accommodation time was observed after a 10-min viewing of 3-D CG movies with a 3DD. 10 The comparison between 3-D viewing and 2-D viewing in this study suggested that the effect on the human visual system was stronger in 3-D viewing with an eyeglass-free 3DD than in 2-D viewing with a 2DD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This result was in accordance with our previous report 5 on 2DD. A similar result has been reported from another laboratory, 10 where a systematic prolongation of accommodation time was observed after a 10-min viewing of 3-D CG movies with a 3DD. 10 The comparison between 3-D viewing and 2-D viewing in this study suggested that the effect on the human visual system was stronger in 3-D viewing with an eyeglass-free 3DD than in 2-D viewing with a 2DD.…”
Section: Discussionsupporting
confidence: 84%
“…A similar result has been reported from another laboratory, 10 where a systematic prolongation of accommodation time was observed after a 10-min viewing of 3-D CG movies with a 3DD. 10 The comparison between 3-D viewing and 2-D viewing in this study suggested that the effect on the human visual system was stronger in 3-D viewing with an eyeglass-free 3DD than in 2-D viewing with a 2DD. We attribute the enhancement of the effect with a 3DD to the discrepancy between accommodation and vergence during the 3-D viewing, because the other conditions were carefully randomized.…”
Section: Discussionsupporting
confidence: 84%
“…tive tension in Korean adults immediately after computer work. [25] Some decrease of AA and AF after computer work for 2 h was also reported by Saito et al [26] In addition, it was found that a shorter interval of computer work, such as 20 min, induced dry eye, which can lead to severe asthenopia. [27] However, findings obtained after a VDT work such as a CRT monitor may not be directly applied for suggesting the change of accommodative function after smartphone use because ergonomic workstation and video display technology have been continuously improved since these earlier studies.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4][12][13][14][15] Bu şikayetler görsel ve oküler yüzey hasarına bağlı semptomlar olarak iki ana gruba ayrılmaktadır. Uzun süreli bilgisayar kullanımı akomodasyon ve verjans fonksiyonlarında bozulmaya yol açmaktadır.…”
Section: Discussionunclassified